If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 5 = 4x + 54 Reorder the terms: 5 + 11x = 4x + 54 Reorder the terms: 5 + 11x = 54 + 4x Solving 5 + 11x = 54 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5 + 11x + -4x = 54 + 4x + -4x Combine like terms: 11x + -4x = 7x 5 + 7x = 54 + 4x + -4x Combine like terms: 4x + -4x = 0 5 + 7x = 54 + 0 5 + 7x = 54 Add '-5' to each side of the equation. 5 + -5 + 7x = 54 + -5 Combine like terms: 5 + -5 = 0 0 + 7x = 54 + -5 7x = 54 + -5 Combine like terms: 54 + -5 = 49 7x = 49 Divide each side by '7'. x = 7 Simplifying x = 7
| 3+2s-2=9s+11-5s | | 5/2(-11,11) | | 3x+15/2x^2+15x+25 | | 1+7x=10x-22 | | 7+4x=54 | | .3(2x-5)=3 | | 2x-7=4/(2x-7) | | 21=17+z/2 | | x(2*2-5)=3 | | 6x/2=4 | | x(2*7-5)=3 | | 3=2x-16 | | w+14=22 | | x(2*9.5-5)=3 | | x(2*3.5-5)=3 | | X(2x+5)=12 | | (6/m+5)+7/m=((3m+5)/(m^2+5m)) | | 52-8x=12x | | 5t+8t=117 | | 8(3-x)-5=-3(3-2x) | | x/14=-27 | | 15-2h=6 | | 5.7q-2.5-5.3q=-0.6q-2.6 | | 4x-18=5+5 | | 5/4x-4/3y=-5/6 | | 2/3x+3/4y=1 | | 1/2x-y=-1/1 | | 5/2x/1/3y=1 | | 5.8q-4.4-5.3q=0.5q-4.1 | | 5.9q-4.4-5.3q=0.5q-4.1 | | 40x+10=2 | | 40x+5=2 |